(untitled) (Anclajes, 2020)
This article takes as a starting point the violence being inflicted through the current United States regime of deportation on male migrants, with the aim of understanding the precarious masculinities consequently taking form within this population. This article presents an analysis of two digital stories from the Humanizing Deportation project, both narrated by men who after being deported lived or have lived several years in precarious conditions on the streets of Tijuana. Migration is proposed as an escape, and deportation as an expulsion within the violence system that has been called the border industrial complex. Deportation represents a brutal and destructive blow that rather than inciting manifestations of the excesses of machismo, it activates a sentimentalized masculinity, which seems to tie deported men to the border, or to the streets running along the border wall, where they maximize proximity to their families, but live exposed to everyday violence. These masculinities are not doubt damaged, but not paralyzed as in some moments these men seem to exercise an infrapolitics that might be understood as an extension of the kind of agency that underlies their escape.